PL02 Resolving conflicts in the multimorbid consultation: how do general practitioners balance diseases, drugs and the views of other doctors?. (2nd September 2014) - Sinnott, CS; Mc Hugh, S; Boyce, M; Bradley, C
Abstract : Background: Multimorbidity poses many dilemmas for healthcare provision, research and educational innovation. This study explores how general practitioners (GPs) currently deal with challenges in the management of multimorbid patients, with a view to identifying targets suitable for professional-orientated interventions to optimise multimorbidity care. Methods: Design: In-depth qualitative interviews incorporating chart stimulated recall, a clinical assessment tool that uses a medical chart to stimulate a physician's recall of a case and its management. Setting: Primary care in the Republic of Ireland. Participants: GPs purposively sampled from continuing professional development groups, using sampling criteria of: length of time qualified; location (rural/urban); and practice size (single/group). Analysis: Interviews were coded using the grounded theory method of constant comparison and theory was developed iteratively. Results: Twenty GPs were interviewed on a total of 51 patient cases. In multimorbid patients perceived as 'stable', even those with high levels of polypharmacy, the default position for GPs was to 'maintain the status quo'. This approach of not changing medications, unless there was clear evidence of harm, arose from GP fear that future events would be linked to the act of removing medications or the act would lead to patient perception of withdrawal of care. For cases with a changing disease trajectory, GPs integrated information from multiple sources, such as the patient, specialists and evidence based medicine. Difficulties arose when this information conflicted. GPs responded to this scenario by 'satisficing' with respect to chronic disease targets; 'broadening the loop' to increase the relative input of other healthcare professionals; 'negotiation' with specialist or patient, or GP acting as 'final arbitrator'. Conflicts most commonly arose when GPs were isolated from other generalists, or had difficulties in the doctor-patient relationship. Conclusion: This study identified potential weaknesses in the decision making process in multimorbidity, which related to lack of GP empowerment, access to professional support, and communication with patients. These novel findings will inform the development of a professional-orientated intervention, to assist GPs in the provision of multimorbidity care.